Reflections of God's holy land : a personal journey through Israel - Everson, Eva Marie; Vamosh, Miriam Feinberg (Nashville, Tenn. : Thomas Nelson, 2008)
Describes the author's tour of biblical sites in Israel with photographs, brief histories of each site using the Bible and the tour guide's knowledge of Israel, and commentaries from the author.
Keywords: Everson, Eva Marie -- Travel -- Israel; Vamosh, Miriam Feinberg -- Travel -- Israel; Israel -- Description and travel; Israel -- History -- Religious aspects -- Christianity; Israel -- Pictorial works